2015
DOI: 10.3892/or.2015.4506
|View full text |Cite
|
Sign up to set email alerts
|

Dual inhibition of COX-2/5-LOX blocks colon cancer proliferation, migration and invasion in vitro

Abstract: Inflammation is emerging as a new hallmark of cancer. Arachidonic acid (AA) metabolism, the family of cyclooxygenases (COXs) and lipoxygenase (LOX) play important roles in AA-related inflammatory cascades. In 94 colorectal cancer samples collected from the Han population, the immunohistochemical results indicated that 68% of the patients with colorectal cancer had a co-expression of both COX-2 and 5-LOX, while both displayed low expression in the matched normal tissues. In cell lines, three colorectal cancer c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 33 publications
2
29
1
1
Order By: Relevance
“…Some studies in CRC cell lines indicated that COX-2 inhibition results in an activation of the 5-lipoxygenase (LOX) pathway (49,50). At least in healthy colon tissue, our findings do not support this hypothesis, as 5-LOX-derived eicosanoid levels remained essentially unaffected upon ASA treatment.…”
Section: Discussioncontrasting
confidence: 84%
“…Some studies in CRC cell lines indicated that COX-2 inhibition results in an activation of the 5-lipoxygenase (LOX) pathway (49,50). At least in healthy colon tissue, our findings do not support this hypothesis, as 5-LOX-derived eicosanoid levels remained essentially unaffected upon ASA treatment.…”
Section: Discussioncontrasting
confidence: 84%
“…It was suggested that Cox-2 is responsible for the regulation of the lipid metabolism [230]. This goes in line with the findings that inhibiting 5-LOX and Cox-2 blocks colon cancer proliferation, migration, as well as invasion in vitro [231]. This may explain why NSAID intake might result in some 50% reduction of the relative CRC risk [232,233] as the combined Cox-1 and Cox-2 activity is increased in CRC [234].…”
Section: Various Lox Enzymessupporting
confidence: 56%
“…7) and 5-LOX is a key enzyme for leukotriene synthesis. This is of particular interest, as increased expression of 5-LOX promotes colon cancer cell proliferation in a direct manner 41,47 . However, more work is needed to determine how MC support colon cancer growth via 5-LOX.…”
Section: Discussionmentioning
confidence: 99%